In vitro and in vivo metabolism of 3-quinuclidinyl benzilate by high-resolution mass spectrometry - Uher, Martin; Mžik, Martin; Karasová, Jana Žďárová; Herman, David; Čechová, Lenka; Dlabková, Alžběta; Mrkvicová, Alena; Hroch, Miloš (Journal of pharmaceutical and biomedical analysis, 2020)
3-Quinuclidinyl benzilate (QNB) is an anticholinergic compound that affects the nervous system. Its hallucinogenic action has led to its potential utility as an incapacitating warfare agent, and it is listed in Schedule 2 by the Organization for the Prohibition of Chemical Weapons. Although this compound has been known for a long time, limited information is available regarding its metabolism and mass spectrometric data of the metabolites, the information that could facilitate the identification of QNB in case of suspected intoxication. To the best of our knowledge, the analytical methods previously described in the literature are based on outdated procedures, which may result in a significantly lower number of observable metabolites. The aim of this work was to obtain deeper insight into QNB biotransformation using a combination of in vitro and in vivo approach. The development of a suitable method for the separation and detection of metabolites using mass spectrometry together with the identification of reliable diagnostic fragments for the unambiguous identification of QNB metabolites in the different biological matrices are also presented in this work. A screening of rat plasma, urine and tissue homogenates revealed 26 new metabolites related to the cytochrome P450 biotransformation pathway, which involves N-oxidation and hydroxylation(s) followed by O-methylation and O-glucuronosylation within phase II of the metabolism. A study showed that the brain is not metabolically active in the case of QNB and that the metabolites do not cross the blood-brain barrier; thus, the toxicodynamic effects are due to QNB itself. In addition, in vitro experiments performed using isolated human liver microsomes revealed N-oxidation as the principal metabolic pathway in human tissue. In light of current global events, the abuse of QNB by terrorists or para-military groups is a real possibility, and our findings may improve the detection systems used in laboratories involved in postexposure investigations.
Keywords: Quinuclidinyl Benzilate; LC-ESI-MS/MS; BZ agent; biotransformace; Rats; mozek; Biotransformation; Animals; QNB; 3-Quinuclidinyl benzilate; krysa rodu Rattus; Metabolism; hmotnostní spektrometrie; chinuklidinylbenzilát; Brain; zvířata; Mass Spectrometry